Meeting support system / Hon Tian Yang - Hon, Tian Yang (2001)
This final year project is compulsory for all student of Faculty Computer Science and Information Technology, University Malaya to graduate, and hoping that with this final year project, students can expose to the real working life environment. This project will provide with an attractive and user-friendly interface that can be used by officers and lecturers in FSKTM for preparing and initializing meeting purposes. The project was carried out based on the Prototyping Model approach. This approach was selected because it is able to represent the numerous activities needed to develop this project. Besides, it has a systematic structure that can guide you through the development of the project. The development tools for this project are Microsoft Visual Interdev 6.0, Microsoft Personal Web Sever 4.0, VBScript, Adobe Photoshop and so on. Microsoft Visual Interdev is used to build web page for up loaded to Internet using ASP and HTML. Microsoft Personal Web Sever 4.0 and Microsoft Access are used for prototyping development where as images editor such as Adobe PhotoShop 5.0 is used for web page design.